2010
DOI: 10.1603/en09210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reproductive Mode on Host Plant Utilization of Melon Aphid (Hemiptera: Aphididae)

Abstract: Variation in the reproductive mode of melon aphid Aphis gossypii Glover occurred on the large geographic scale, but the performance of different reproductive modes to use host plant is poorly understood. Life tables of melon aphid population that undergo the anholocyclic, androcyclic, and intermediate reproductive mode were conducted on different host plants. The results showed that the anholocyclic and androcyclic strains could become adults and produce offspring on cotton Gossypium hirsutum L., whereas the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(36 reference statements)
0
4
1
Order By: Relevance
“…Our VBM analysis also identified a second cluster, comprising the right superior and middle temporal gyri, in which greater volumes were associated with better response. This result contradicts two previous studies that found lower volumes in these brain regions associated with better antidepressant treatment response (Liu and Gao, 2010; Sämann et al, 2013). However, a recent meta-analysis stressed the need to investigate the relation between right temporal areas and response in depression, provided that only these two studies reported significant associations, that the direction of the effect is opposite to what is usually found and expected, and that no analogous result has been identified for studies investigating structural correlates or treatment response to ECT or cognitive behavioral therapy (CBD) (Enneking et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our VBM analysis also identified a second cluster, comprising the right superior and middle temporal gyri, in which greater volumes were associated with better response. This result contradicts two previous studies that found lower volumes in these brain regions associated with better antidepressant treatment response (Liu and Gao, 2010; Sämann et al, 2013). However, a recent meta-analysis stressed the need to investigate the relation between right temporal areas and response in depression, provided that only these two studies reported significant associations, that the direction of the effect is opposite to what is usually found and expected, and that no analogous result has been identified for studies investigating structural correlates or treatment response to ECT or cognitive behavioral therapy (CBD) (Enneking et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…As suggested by a recent review, generally, lower GM volumes appear to be linked to worse treatment outcomes (Kang and Cho, 2020). On the other hand, a few studies have associated lower baseline GM volumes with better treatment response, particularly in right temporal regions (Liu and Gao, 2010; Sämann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbit-specialized Ando et al, 1992;Meng & Li, 2001;Wu et al, 2013 Cotton 2008; Liu & Gao, 2010). In Europe, the reproductive mode of A. gossypii was considered to be exclusively parthenogenetic (Fuller et al, 1999;Blackman & Eastop, 2000).…”
Section: Population Establishment Difficultmentioning
confidence: 99%
“…In China, the cotton‐specialized A. gossypii is known to be holocyclic (Zhang & Zhong, ), but the cucurbit‐specialized form was assumed to be anholocyclic. This is because it was easy to produce sexual forms of the cotton‐specialized aphids under short photoperiods and lower temperature conditions, while this proved impossible for cucurbit‐specialized forms (Zhang & Zhong, ; Gao & Liu, ; Liu & Gao, ). In Europe, the reproductive mode of A. gossypii was considered to be exclusively parthenogenetic (Fuller et al ., ; Blackman & Eastop, ).…”
Section: Introductionmentioning
confidence: 99%
“…The reproduction mode of A. gossypii was exclusive clonal in Europe, and it was mostly asexual with only once sexual in China and some other cool areas [14],[23],[24]. The parthenogenesis on a specific host plant during the annual cycle facilitated the formation and maintenance of host specialization [19],[25] [26]. The performances in host use, reproduction mode and genotype showed that the cotton- and cucurbits-specialized aphids had greater ecological and genetic divergence.…”
Section: Introductionmentioning
confidence: 99%